Interstellar spectral features and telluric absorption lines - Kuźmicz, A.; Wszołek, B. (Advances in Astronomy and Space Physics, 2012)
In good quality spectra of stars the weak interstellar absorption lines may be substantially contaminated by telluric lines. Many telluric lines may also simulate interstellar absorptions. To avoid undesirable telluric effects during searches for interstellar absorptions, especially for diffuse interstellar bands (DIBs), we looked for all accessible catalogued telluric absorption lines in our spectra which contain DIBs. We investigated the echelle spectra of two stars, oPer and βTau, to revise the list of DIBs in oPer direction known from literature. We found that many telluric features simulate interstellar absorptions. We present the example parts of spectra to visualize this problem.